Ca2+‐induced structural changes and intramolecular interactions in N‐terminal region of diacylglycerol kinase alpha. (16th June 2022) - Takahashi, Daisuke; Yonezawa, Kento; Okizaki, Yuki; Caaveiro, Jose M. M.; Ueda, Tadashi; Shimada, Atsushi; Sakane, Fumio; Shimizu, Nobutaka
Abstract: Diacylglycerol kinases (DGKs) are multi‐domain lipid kinases that modulate the levels of lipid messengers, diacylglycerol, and phosphatidic acid. Recently, increasing attention has been paid to its α isozyme (DGKα) as a potential target for cancer immunotherapy. However, little progress has been made on the structural biology of DGKs, and a detailed understanding of the Ca 2+ ‐triggered activation of DGKα, for which the N‐terminal domains likely play a critical role, remains unclear. We have recently shown that Ca 2+ binding to DGKα‐EF induces conformational changes from a protease‐susceptible "open" conformation in the apo state to a well‐folded one in its holo state. Here, we further studied the structural properties of DGKα N‐terminal (RVH and EF) domains using a series of biophysical techniques. We first revealed that the N‐terminal RVH domain is a novel Ca 2+ ‐binding domain, but the Ca 2+ ‐induced conformational changes mainly occur in the EF domain. This was corroborated by NMR experiments showing that the EF domain adopts a molten‐globule like structure in the apo state. Further analyses using SEC‐SAXS and NMR indicate that the partially unfolded EF domain interacts with RVH domain, likely via hydrophobic interactions in the absence of Ca 2+, and this interaction is modified in the presence of Ca 2+ . Taken together, these results present novel insights into the structural rearrangement of DGKα N‐terminal domains upon binding to Ca 2+, which is essential for the activation of the enzyme.